Elemental sulfur improves growth and phytoremediative ability of wheat grown in lead-contaminated calcareous soil. Issue 10 (2nd October 2016) - Saifullah,; Khan, Muhammad Naeem; Iqbal, Muhammad; Naeem, Asif; Bibi, Sadia; Waraich, Ejaz Ahmad; Dahlawi, Saad
ABSTRACT: Little is known about the effect of elemental sulfur on lead uptake and its toxicity in wheat. A pot experiment was conducted with the purpose to examine the impact of sulfur on improving Pb solubility in soil, and uptake and accumulation in wheat plants. The effect of three levels of lead (0, 50, and 100 mg/kg soil) and sulfur (0, 150, and 300 mmol/kg soil) was tested in all possible combinations. Root dry matter, straw, and grain yields, and the photosynthetic and transpiration rates decreased significantly with increase in the concentration of Pb in the soil. However, sulfur fertilization in the presence of Pb improved the photosynthetic and transpiration rates and consequently increased the straw and grain yields of wheat. It also enhanced Pb accumulation in roots, its translocation from roots to shoot, and accumulation in grain. S and Zn contents of different plant parts were also enhanced. Thus, by mitigating the toxic effect of Pb and improving wheat growth, sulfur enhances Pb accumulation by the aboveground plant parts and hence the phytoextraction capacity of wheat. However, total accumulation of Pb shows that wheat plant cannot be considered as a suitable candidate for phytoremediation.